Do trust and power moderate each other in relation to tax compliance? - Mas’ud, Abdulsalam; Abd Manaf, Nor Aziah; Saad, Natrah (Elsevier Ltd., 2014)
This paper examines the assumptions of the Slippery Slope Framework using cross-country data; an area which has been neglected since the emergence of the framework in 2008. Several studies in this area have tested the assumption of the framework using primary data collected through survey with students or real taxpayers as subjects. Hence, this study tests these assumptions using statistical data generated from an institutional database. The empirical result from our sample indicates that trust in and power of authorities strongly interacts in explaining tax compliance.